Experiences of Aggressive Behavior Patient after Physical Restraint in Mental Hospital, A Qualitative Study - Iyus Yosep; Ati Surya Mediawati; Ai Mardhiyah (STIKep PPNI Jawa Barat, 2022)
Aims. The prevalence of Violence in nurses and patients is an important issue today. One of the handlings of violent patients in mental hospitals is restraint. Restraint becomes a difficult choice for nurses in mental hospitals. This choice is still made with ethical considerations to prevent a worse risk. Restraints can violate patient rights. But if not done can threaten the environment. After physical restraint the patient has special experiences that need to be evaluated by the mental health nurse. Purpose. The purpose of this study was to describe the experience of patients with physical violence after restraint at the Mental Hospital, West Java. Methods. The informant selection technique used in this study was purposive sampling. The number of informants in this study was six patients. Patients were selected based on two inclusion criteria, first; have ever done physical violence, secondly, have experienced physical restraint. Patients have been selected by the head of the ward and approved by the nursing ethics board. Data was collected through focus group discussions (FGD). Data was recorded using an audiovisual camera. The discussion was conducted over three sessions, in three days, each for 60 minutes. The collected data is typed verbatim. The thematic analysis used in this study refer to six steps qualitative analysis. Result. There are six themes that arise in the client's response to violent behavior during physical restraint. It includes ignoring the patient's basic needs, Feelings of anger and irritation, thinking that there is no perceived positive influence, controlling his behavior for fear of the next physical restraint, Surrender to the conditions experienced, Feelings of relief and joy after not undergoing physical restraint, there is a feeling of revenge and want to take revenge. Conclusion. The patient's experience with physical violence after the act of restraint reveals the occurrence of neglect of basic human needs, the emergence of feelings of anger and irritation and thinking that restraint is of no benefit. After going through the angry phase, there is a sense of resignation to the patient and the informant's efforts to control his behavior for fear of getting physical restraint again. However, there is also a feeling of resentment that is triggered by the experience of being treated inhumanely.